Pemanfaatan Pojok Literasi Sekolah Untuk Peningkatan Kemampuan Literasi Sastra Siswa SMP Islam Al-Kholili Kota Probolinggo - Tjahyadi, Indra; Andayani, Sri; Sutrisno, Adi; Mulyono, Sugeng Edy (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2024)
Literacy plays a very important role in improving students' knowledge skills because it is the basis of the learning process.Literacy not only allows students to understand texts, both academic and everyday, but can also improve students' ability toanalyze, evaluate, and distinguish relevant and valid information. Literacy is the main foundation in education. Investment inimproving students' literacy, whether through reading activities, writing training, or discussions, will have a long-term impact. on improving their knowledge and skills. Therefore, it is important for parents, teachers, and educational institutions to payserious attention to the development of literacy from an early age. This Community Service Activity focuses on utilizing theschool literacy corner as a medium to improve students' literacy skills. This activity was carried out at SMP Islam Al-Kholili,Probolinggo City from September to December 2024. The targets of this community service activity were teachers and studentsat SMP Islam Al-K.holili, Probolinggo City. From the implementation of Community Service activities, it was found that theexistence of a literacy corner at SMP Islam Al-Kholili, Probolinggo City can not only increase students' interest in reading, butalso improve students' ability to understand and evaluate the contents of literature textbooks. In addition, it can also create aneffective teaching and learning atmosphere at SMP Islam Al-Kholili, Probolinggo City.